If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -6 = -13 + -5y Reorder the terms: -6 + 2y = -13 + -5y Solving -6 + 2y = -13 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. -6 + 2y + 5y = -13 + -5y + 5y Combine like terms: 2y + 5y = 7y -6 + 7y = -13 + -5y + 5y Combine like terms: -5y + 5y = 0 -6 + 7y = -13 + 0 -6 + 7y = -13 Add '6' to each side of the equation. -6 + 6 + 7y = -13 + 6 Combine like terms: -6 + 6 = 0 0 + 7y = -13 + 6 7y = -13 + 6 Combine like terms: -13 + 6 = -7 7y = -7 Divide each side by '7'. y = -1 Simplifying y = -1
| 3x+64=5x | | (5x+7)(4+6)= | | 144+3x-9=180 | | 2x+9=55 | | (3x-8x)+12=-5x+12 | | 3x+76=7x | | 29x+16x=180 | | 36x^4-25= | | 165+3x-12=180 | | 135=3x+12 | | 119+6x=121+4x | | 108=3x | | 2x+93=5x | | 270-12x=6x | | -9y+7=18 | | 161+2x-19=180 | | 117=3x+18 | | 135=3x | | 9t+15=4 | | 72=3x+3 | | 14-5t-15=8t+13-6t | | 13=3b+25 | | 17x+x=180 | | 9+6r=69 | | =(7b^2+2b-5)-(3b^2+2b-6) | | 14-5x-15=8x+13-6x | | 2x+72=5x | | 7xy+9xy=96whatisy | | 80=100-9.1(x-1.9) | | 4g+7=-5g-1+g | | 0.8=100-9.1(x-1.9) | | =(-2p^3-5p+7)+(-4p^2+8p+2) |